Atypical Presentation of Multiple Myeloma in a 26 Years-Old Young Male with Acute Renal Impairment - Strakosha, Arjana; Cadri, Vilma; Rista, Elvana; Pasko, Nevi; Ivanaj, Arben; Kola, Ina; Guy, Ali; Musa, Juna (Archives of Clinical and Medical Case Reports, 2020)
Multiple myeloma is characterized by a malignant proliferation of bone marrow plasma cells leading to the production of monoclonal paraproteins in the blood and urine. This pathology occurs more often in men with an average of 65 years old and very rarely in younger patients. We present here a case of a 26 years-old male diagnosed with multiple myeloma. He presented with acute renal impairment (DRA) as the first sign of multiple myeloma. Laboratory data showed the presence of monoclonal proliferation of immunoglobulins with increased serum level of light chains and 34% presence of plasma cells in myelograms. Renal biopsy confirmed the diagnosis of acute renal injury from light chain deposition. The patient started treatment with chemotherapy and immunosuppression that was accompanied by clinical improvement and stabilization of renal function. By presenting this clinical case, we want to show that multiple myeloma can be the cause of acute alteration of renal function in a very young patient.